Severe Acute Maternal Morbidity and Intensive Care in Paropakar Maternity and Women’s Hospital - Upadhyaya, I; Chaudhary, P (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: Maternal morbidity occurs due to complications arising in pregnancy or within 42 days of delivery. Women with acute severe morbidity require admission in the intensive care unit (ICU). This study was done to explore the profile of those women requiring intensive care. Methods: A study was conducted at Paropakar Maternity and Women’s Hospital in which records of patients admitted in Maternal Intensive Care Unit (MICU) were evaluated for demographics, disease responsible for critical illness, complications that prompted MICU admissions, interventions required, length of MICU stay and resulting maternal morbidity and mortality. Results: Over the study period, 159 obstetric patients were transferred to MICU, representing 2.23% of 7109 deliveries. Hypertensive disorders of pregnancy (50%) and postpartum haemorrhage (14.46 %) were the two major obstetrical conditions responsible admission into MICU. Conclusions: Auditing of severe maternal morbidity will improve the quality of obstetric care and decrease the incidence of maternal morbidity and maternal mortality. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 2 / Issue 16 / July-Dec, 2013 / 38-41 DOI: http://dx.doi.org/10.3126/njog.v8i2.9768